2022
DOI: 10.1038/s41467-022-34428-w
|View full text |Cite
|
Sign up to set email alerts
|

Tumor factors stimulate lysosomal degradation of tumor antigens and undermine their cross-presentation in lung cancer

Abstract: Activities of dendritic cells (DCs) that present tumor antigens are often suppressed in tumors. Here we report that this suppression is induced by tumor microenvironment-derived factors, which activate the activating transcription factor-3 (ATF3) transcription factor and downregulate cholesterol 25-hydroxylase (CH25H). Loss of CH25H in antigen presenting cells isolated from human lung tumors is associated with tumor growth and lung cancer progression. Accordingly, mice lacking CH25H in DCs exhibit an accelerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…The downregulation of CH25H appears to facilitate membrane fusion between endophagosomes and lysosomes in DCs, hastening lysosomal degradation and thereby limiting the crosspresentation of tumor antigens. 116 However, the administration of the STING agonist MSA-2 has been found to decrease lysosomal activity in DCs, subsequently restoring their ability to cross-present antigens. This process enhances the therapeutic effectiveness of PD-1 blockade in tumor models, and this enhancement is dependent on the presence of CH25H.…”
Section: Genes Governing Other Immune Cell Functions In the Tmementioning
confidence: 99%
See 1 more Smart Citation
“…The downregulation of CH25H appears to facilitate membrane fusion between endophagosomes and lysosomes in DCs, hastening lysosomal degradation and thereby limiting the crosspresentation of tumor antigens. 116 However, the administration of the STING agonist MSA-2 has been found to decrease lysosomal activity in DCs, subsequently restoring their ability to cross-present antigens. This process enhances the therapeutic effectiveness of PD-1 blockade in tumor models, and this enhancement is dependent on the presence of CH25H.…”
Section: Genes Governing Other Immune Cell Functions In the Tmementioning
confidence: 99%
“…Experimental models in mice have shown that the absence of CH25H in DCs results in accelerated tumor growth, diminished infiltration, and reduced activation of intratumoral CD8 + T cells. The downregulation of CH25H appears to facilitate membrane fusion between endophagosomes and lysosomes in DCs, hastening lysosomal degradation and thereby limiting the cross‐presentation of tumor antigens 116 . However, the administration of the STING agonist MSA‐2 has been found to decrease lysosomal activity in DCs, subsequently restoring their ability to cross‐present antigens.…”
Section: Potential Targets Modulating Tumor Immune Responsementioning
confidence: 99%
“…14−18 Lysosome, as a membrane-bound organelle in animal cells, is an important storage place for ATP, and lysosome can respond to external stimuli by exocytosis through releasing ATP. 19−21 In the tumor site and microenvironment often accompanied by increased ATP levels, 22,23 it is difficult to distinguish ATP in lysosome from ATP in other parts of cells according to previous research. 19 At present, a series of fluorescent probes have been developed to monitor ATP in cells and tissues, but using most of them, the result that only ATP in lysozyme has fluorescence performance cannot be achieved.…”
mentioning
confidence: 99%
“…Adenosine triphosphate (ATP) is a high-energy phosphate compound connected by adenine, ribose, and three phosphate groups, which is called the “energy currency” of the organism. Lysosome, as a membrane-bound organelle in animal cells, is an important storage place for ATP, and lysosome can respond to external stimuli by exocytosis through releasing ATP. In the tumor site and microenvironment often accompanied by increased ATP levels, , it is difficult to distinguish ATP in lysosome from ATP in other parts of cells according to previous research . At present, a series of fluorescent probes have been developed to monitor ATP in cells and tissues, but using most of them, the result that only ATP in lysozyme has fluorescence performance cannot be achieved. , The commonly used Zn (DPA) complex has rapid response ability and high sensitivity, but its strong interaction with phosphate groups causes ADP interference and counteracts its specificity to ATP .…”
mentioning
confidence: 99%